Exploring Customer Relationship Management to Enhance the Loyalty of Customers in Online Fashion Commerce - Rohman, Fatchur; Triangga, Bigraf; Hairul, Riandika Noval (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The objective of the current study is to develop a conceptual framework that could explain the role of customer relationship management in enhancing the loyalty of customers to online fashion commerce platforms (websites or mobile apps). An explanatory research design was conducted to achieve the objective of the current research. A total of 235 samples from online fashion commerce in Indonesia participated via offline and online surveys. The collected data was analyzed using SEM-PLS. Three validation steps were utilized: outer model analysis, inner model analysis, and hypothesis testing. The results of the outer model analysis confirmed that all the items used to measure each of the variables in the model were a good fit. In addition, the results of the inner model analysis also validated the robustness of the proposed conceptual framework in explaining the relationships between the variables. The first key finding of the current research is that a seamless shopping experience does not directly influence the loyalty of online fashion commerce customers. However, interesting results were found regarding the role of customer trust and customer satisfaction in this relationship. These two variables fully mediated the influence of a seamless shopping experience on customer loyalty.